2016
DOI: 10.1088/2040-8978/18/3/035005
|View full text |Cite
|
Sign up to set email alerts
|

Plasmonic surface lattice resonances in arrays of metallic nanoparticle dimers

Abstract: Abstract. We investigate the optical response of square arrays of metallic nanoparticles where each lattice site is occupied by two particles, a dimer. In particular we examine the surface lattice resonances arising in these structures when the inplane dipole moments associated with the plasmon modes of the nanoparticles couple together. The addition of a second particle to the basis leads to a more complex optical response, one that is anisotropic in the plane of the array. Extinction spectra are recorded at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 49 publications
2
47
0
1
Order By: Relevance
“…At the same time, calculations in the parallel situation also indicate narrow resonances, albeit slightly wider. 91 The results in Figure 3 (b) indicate that for a 2D array the spectral position of the resonance scales as the particle separation rises in a manner that is similar to that for the 1D chains, albeit with resonances that are slightly broader. Zou et al also found that other wavevector and polarization choices led, for a given spacing, to broader line-shapes.…”
Section: Early Theoretical Studies Of Diffractively Coupled Localizedmentioning
confidence: 76%
“…At the same time, calculations in the parallel situation also indicate narrow resonances, albeit slightly wider. 91 The results in Figure 3 (b) indicate that for a 2D array the spectral position of the resonance scales as the particle separation rises in a manner that is similar to that for the 1D chains, albeit with resonances that are slightly broader. Zou et al also found that other wavevector and polarization choices led, for a given spacing, to broader line-shapes.…”
Section: Early Theoretical Studies Of Diffractively Coupled Localizedmentioning
confidence: 76%
“…. , k max + 1 do 2 Compute r k = aB kmax+νmax r k−1 where B kmax+νmax+1 is given by (31) end 3 Set q = J T e 1 where J = J µ ∈ C kmax×kmax given in (24) for i = 1, . .…”
Section: Numerical Simulationsmentioning
confidence: 99%
“…Adjacent resonators are of particular interest as they exhibit oscillatory modes that cannot be excited by single resonators and have interesting physical properties such as special mode symmetries (fanoresonances) that may exhibit strong coupling, and higher Q-factors [24,41,39].…”
Section: Disk Dimer Problemmentioning
confidence: 99%
“…Another way to influence LSPRs in nanoparticles is by bringing them in close vicinity to one another to create coupled modes via resonant plasmon scattering. It is also possible to generate constructive interferences of the scattered fields of all the nanoparticles in an arrangement, also referred to as surface lattice resonances (SLRs) or superlattice resonances in case of hierarchical arrays . These collective resonances can impact the existing LSPR of the isolated object or even give rise to new features in the optical response of the particle assembly.…”
Section: Introductionmentioning
confidence: 99%